Faculty Perspective on Curriculum Internationalization - Khegay, Evgeniya; Smotherson, Brittany (Journal of International Students, 2026)
Curriculum internationalization in higher education affects faculty, as they design and then deliver curricula. Therefore, experiences of faculty who navigate these changes are important to consider for an effective internationalization process. This research aims to explore faculty insights, including challenges they face, their identity, and opportunities of curriculum internationalization. Narrative interviews were implemented to collect the data. Faculty narratives were then transcribed, and inductive coding was used for analysis. To critically discuss the power dynamics, a radical feminist lens was used. Key findings demonstrate institutional barriers, including stigmatized sensitive topics that limit open discussions and hierarchies within the universities. Faculty positionality and their identities also affect their pedagogical practices and approaches, as well as their perception of curriculum internationalization. However, despite the challenges, faculty discuss opportunities for inclusion, raising global awareness, and curriculum decolonization. The findings highlight the need for institutional support and critical approaches in pedagogy.